Analysis of Peptides and Proteins by Electrophoretic Techniques - Herrero-Martínez, José Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The characterization of peptides and proteins is central to understanding their function and expression in biological matrices. Moreover, these macromolecules are important biomarkers of many human diseases. In recent years, the performance of separation techniques based on electromigration have significantly increased. The development of microdevices has reduced sample consumption and waste production while high-sensitivity detectors, such as mass spectrometry (MS) or laser-induced fluorescence (LIF), have significantly improved with regards to separation efficiency and detection limits. All of these advancements have led to appreciably enlarged fields of application. Nowadays, a multitude of studies using separation techniques based on electromigration to study proteins and peptides from numerous real matrices are available in the literature. This Special Issue covers the most recent knowledge and advances in the study of peptides and proteins using several electrophoresis techniques, as well as the characterization of relevant proteins and peptides in application areas such as clinical studies, functional foods, and toxicology.